The role of high-pressure coolant in the wear characteristics of WC-Co tools during the cutting of Ti-6Al-4V - Stolf, Pietro; Paiva, Jose Mario; Ahmed, Yassmin Seid; Endrino, José L.; Goel, Saurav; Veldhuis, Stephen C. (Elsevier, 2019)
Aeronautic applications have been making use of titanium alloys for decades. Ti–6Al–4V is one of the most commonly applied alloys, and although its mechanical properties warrant its acceptance for many applications, the machinability of this alloy remains a challenge. So far, the most successful technique in facilitating this alloy's machining has been the application of High-Pressure Coolant Supply (HPC) on account of its influence on the tribological aspects of the cutting operation. On that premise, this work employs experimental and computational resources to advance the current understanding of the wear mechanism in terms of the tool-chip contact conditions and establish a correlation between coolant pressure, cutting speed, tool life, cutting forces, and chip formation when machining Ti–6Al–4V with HPC supply. Results showed that HPC plays a role in the reduction of tool-chip temperature profiles and contact stresses, positively impacting tool flank wear, oxidation levels and chip formation, also improving chip breakability.
Keywords: Tool wear; Titanium; High-pressure coolant; Tribology; Chip formation; FEA